Proteasome Inhibition Prevents Development of Experimental Dermal Fibrosis - Koca, Suleyman Serdar; Ozgen, Metin; Dagli, Ferda; Tuzcu, Mehmet; Ozercan, Ibrahim Hanifi; Şahin, Kazım; Isik, Ahmet (Springer/Plenum Publishers, 2012)
Scleroderma is a chronic fibrotic disorder. Bortezomib, a proteasome inhibitor, is reported to attenuate experimentally induced renal and cardiac fibrosis. This study aimed to evaluate the preventive and therapeutic efficacies of bortezomib on a bleomycin (BLM)-induced scleroderma model. Dermal fibrosis was induced in Balb/c mice by subcutaneous BLM (100 mu g/day) injections. Bortezomib (1.6 mg/kg twice/week) was applied intraperitoneally to BLM-injected mice during the first 3 weeks for preventive interventions and in the second 3 weeks for therapeutic interventions. IL-4 and TGF-beta 1 serum levels, dermal thicknesses, dermal inflammatory cell counts, and alpha-SMA-positive fibroblastic cell counts were determined, and type-I collagen, NF-kappa Bp65, I-kappa B alpha, and JNK1 expressions were assessed. BLM applications increased serum IL-4 level, dermal inflammatory cell counts, alpha-SMA-positive cell counts, expression of type-I collagen, NF-kappa B, and JNK1, and dermal thickness in early stage of fibrosis, but serum IL-4 level and dermal inflammatory cell counts showed no increases in later stages. As a preventive intervention, bortezomib decreased dermal thickness, inflammatory cell infiltrations, fibroblastic activity, and expression of type-I collagen, NF-kappa B, and JNK1, but did not decrease fibroblastic activity and dermal thickness at later stages of fibrosis. Inflammatory status is prominent in the early stage of dermal fibrosis, but declines at later stages. In BLM-induced dermal fibrosis, bortezomib has a preventive anti-fibrotic and anti-inflammatory efficacy, but has no therapeutic anti-fibrotic efficacy in preexisting tissue fibrosis. These findings suggest that the effect of proteasome inhibition in early stages of dermal fibrosis may be related to its anti-inflammatory effects.
Keywords: scleroderma; dermal fibrosis; proteasome inhibition